2016
DOI: 10.1016/j.ygyno.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of the ACS NSQIP surgical risk calculator in gynecologic oncology patients undergoing laparotomy

Abstract: Objective The objective of this study was to evaluate the ability of the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) surgical risk calculator to predict complications in gynecologic oncology patients undergoing laparotomy. Methods A chart review of patients who underwent laparotomy on the gynecologic oncology service at a single academic hospital from January 2009 to December 2013 was performed. Preoperative variables were abstracted and NSQIP surgical risk scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…However, the aforementioned models cannot reliably be used in gynecological oncology [21,23,24]. Apparently, the risk factors for postoperative morbidity differs based on the surgical sites and the type of procedures [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, the aforementioned models cannot reliably be used in gynecological oncology [21,23,24]. Apparently, the risk factors for postoperative morbidity differs based on the surgical sites and the type of procedures [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study in a gynecologic oncology population demonstrated that the calculator was able to predict the risk of death and cardiac complications, but was not accurate for other surgical complications. 29 The SGO/ASCO Panel looks forward to reviewing validated and tested, user-friendly risk prediction tools when they are available, but at present, none can be fully recommended.…”
Section: Recommendationsmentioning
confidence: 99%
“…For our cohort, we looked at the ACS NSQIP surgical risk calculator. Although the NSQIP surgical risk calculator has been shown to adequately predict specific serious complications, the overall performance of the calculator may be less accurate in gynecologic oncology patients than reported in general surgery patients, suggesting the need for a tailored prediction model in our population ( Rivard et al, 2016 ). In our small cohort, who were deemed medically inoperable and progressed following initial treatment and were treated surgically, the mortality rate was 12.5% (1/8); again, small numbers limit any conclusions.…”
Section: Discussionmentioning
confidence: 99%